2020
DOI: 10.1136/neurintsurg-2019-015347
|View full text |Cite
|
Sign up to set email alerts
|

Balloon anchoring technique forthrombectomyin hostile craniocervical arterial anatomy

Abstract: BackgroundCraniocervical catheter access in large vessel occlusion acute ischemic strokes can be challenging in cases of unfavorable aortic arch/cervical vascular anatomy, leading to lower recanalization rates, increased procedural time and worse clinical outcomes. We aim to demonstrate the feasibility of the balloon-anchoring technique (BAT) that can be attempted before switching to alternative access sites.MethodsRetrospective review of prospectively collected information on 11 patients in which two variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The authors previously reported the improved trackability and stability of BGC during MT with our initial experience of 8F FlowGate2 BGC [ 34 ]. Sharashidze et al [ 22 ] have shown the proximal balloon anchoring with BGC in case with failure of pushing the guidewire into the ICA due to elongation of the arch and tortuosity of the CCA. Balloon inflation of BGC at left CCA enables the positioning of guidewire and co-axial catheter to the left ICA and serial tracing of BGC to the ICA [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors previously reported the improved trackability and stability of BGC during MT with our initial experience of 8F FlowGate2 BGC [ 34 ]. Sharashidze et al [ 22 ] have shown the proximal balloon anchoring with BGC in case with failure of pushing the guidewire into the ICA due to elongation of the arch and tortuosity of the CCA. Balloon inflation of BGC at left CCA enables the positioning of guidewire and co-axial catheter to the left ICA and serial tracing of BGC to the ICA [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sharashidze et al [ 22 ] have shown the proximal balloon anchoring with BGC in case with failure of pushing the guidewire into the ICA due to elongation of the arch and tortuosity of the CCA. Balloon inflation of BGC at left CCA enables the positioning of guidewire and co-axial catheter to the left ICA and serial tracing of BGC to the ICA [ 22 ]. Anchored BGC may provide a strong support to allow the advancement of the co-axial device to the distal lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The balloon anchoring technique is one of them, and it has been previously reported that it was feasible in various neuroendovascular therapies. 11,12 However, to the best of our knowledge, there are no reports of the use of this method in sinus stenting cases.…”
Section: Discussionmentioning
confidence: 99%
“…Проблему трудной катетеризации, например при дуге аорты III типа, пытались решить, используя при ТФД баллонный гайд-катетер в качестве якоря для облегчения продвижения катетера для тромбэктомии [23].…”
Section: альтернативные доступы при стентированииunclassified